Faktor Risiko Kejadian Ikterus Neonatorum - Nimas Anggie Auliasari; Risa Etika; Ilya Krisnana; Pudji Lestari (Pediomaternal Nursing Journal, 2019)
Introduction: Neonatal jaundice is a clinical manifestation in neonates characterized by yellow coloration of the skin and sclera due to the accumulation of excess unconjugated bilirubin production in the tissues. Based on the data in the NICU of Dr. Soetomo Hospital, 46.8% of 844 neonates had neonatal jaundice. Therefore, this study is intended to analyze the risk factors associated with the incidence of neonatal jaundice.Methods: This study used observational analytic method with case control approach. There are 84 neonates used as samples taken with sequential sampling. The independent variables are ABO incompatibility, prematurity, Low Birth Weight, asphyxia, and history of Diabetes Mellitus from the mother. Whereas, the dependent variable is neonatal jaundice. The data are in the form of secondary data from neonates and the mothers, analyzed using the Contingency coefficient with α = 0.05.Results: 85.7% of ABO incompatibility neonates had neonatal jaundice (p = 0.048, OR = 6.833), 57.4% of premature neonates had neonatal jaundice (p = 0.028, OR = 3.077), 42.4% of LBW neonates had neonatal jaundice (p = 0.032, OR = 0.346), 60% of asphyxia neonates had neonatal jaundice (p = 0.500), 85.7% of mother with DM history had neonatal jaundice (p = 0.048, OR = 6.833).Conclusion: There is a relationship between ABO incompatibility, prematurity, LBW, history of DM and neonatal jaundice while there is no relationship between asphyxia and the incidence of neonatal jaundice in Dr. Soetomo Hospital.